A chromosome-scale genome assembly and dense genetic map for Xenopus tropicalis - Mitros, Therese; Lyons, Jessica B.; Session, Adam M.; Jenkins, Jerry; Shu, Shengquiang; Kwon, Taejoon; Lane, Maura; Ng, Connie; Grammer, Timothy C.; Khokha, Mustafa K.; Grimwood, Jane; Schmutz, Jeremy; et al. (Developmental biology, 2019)
The Western clawed frog Xenopus tropicalis is a diploid model system for both frog genetics and developmental biology, complementary to the paleotetraploid X. laevis. Here we report a chromosome-scale assembly of the X. tropicalis genome, improving the previously published draft genome assembly through the use of new assembly algorithms, additional sequence data, and the addition of a dense genetic map. The improved genome enables the mapping of specific traits (e.g., the sex locus or Mendelian mutants) and the characterization of chromosome-scale synteny with other tetrapods. We also report an improved annotation of the genome that integrates deep transcriptome sequence from diverse tissues and stages. The exon-intron structures of these genes are highly conserved relative to both X. laevis and human, as are chromosomal linkages (“synteny”) and local gene order. A network analysis of developmental gene expression will aid future studies. •X. tropicalis genome assembly v9 is chromosome scale and facilitates new analyses.•The enhanced proteome is more complete compared to human.•This proteome enables novel findings when compared with the related frog X. laevis.•Genetic map was used for genome assembly, and mapping sex and a pigmentation mutant.